2012
DOI: 10.1136/bmjopen-2012-000939
|View full text |Cite
|
Sign up to set email alerts
|

Understanding public trust in services provided by community pharmacists relative to those provided by general practitioners: a qualitative study

Abstract: ObjectivesTo apply sociological theories to understand public trust in extended services provided by community pharmacists relative to those provided by general practitioners (GPs).DesignQualitative study involving focus groups with members of the public.SettingThe West of Scotland.Participants26 purposively sampled members of the public were involved in one of five focus groups. The groups were composed to represent known groups of users and non-users of community pharmacy, namely mothers with young children,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
101
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(110 citation statements)
references
References 37 publications
8
101
1
Order By: Relevance
“…Furthermore, they may be unaware of the breadth of the pharmacist's expertise beyond the supply of medication, which is consistent with existing knowledge. 12,13,18,19,47 Our study confirms that further promotion of the pharmacist's role is needed for the entire community. However, a recent paper ascertained that Scottish consumers were inclined to seek professional services from their GP, and an increase in service uptake did not follow on from an increased knowledge of pharmacy services.…”
Section: Discussionsupporting
confidence: 69%
“…Furthermore, they may be unaware of the breadth of the pharmacist's expertise beyond the supply of medication, which is consistent with existing knowledge. 12,13,18,19,47 Our study confirms that further promotion of the pharmacist's role is needed for the entire community. However, a recent paper ascertained that Scottish consumers were inclined to seek professional services from their GP, and an increase in service uptake did not follow on from an increased knowledge of pharmacy services.…”
Section: Discussionsupporting
confidence: 69%
“…[8][9][10] Research findings have confirmed the positive contribution and the potential of the professional performance of pharmacists in providing public-health initiatives. 11 Interestingly, a broadening of this role has been suggested for better involvement in health promotion and prevention activities.…”
Section: Innovations In Pharmacymentioning
confidence: 55%
“…Previous research has shown that these services are important for the development of pharmacist-primary care collaboration. 11,17,20 Overall, findings from this study describe the current use of community pharmacies and the general image towards the role of pharmacists in Iraq.…”
Section: Innovations In Pharmacymentioning
confidence: 99%
See 1 more Smart Citation
“…Performing screening in a familiar setting -inside the general practice -is likely to enhance participation. 2 In addition, counselling and treatment could easily follow screening, as these are already part of usual care.…”
Section: Introductionmentioning
confidence: 99%